A Total systems study on Rapide Auto Service Center - Baquiran, Francis Allan D.; Gito, Gilmour M.; Segundo, Joana Marie O.; Tabucal, Natasha P. (Diliman, Quezon City College of Engineering, 2003)
The following paper is a total systems study on Rapide Auto Service Center. Rapide is a chain of auto service centers that offer certain repair and maintenance services on vehicles. It currently has 10 branches nationwide with 4 other franchise branches. Rapide's mission is "To be the best service center with the best people". Rapide's strengths over its competitors include its coverage, with its large number of branches, its use of genuine parts and its efficient service rendered by its skilled technicians. Rapide has several weaknesses however, including the large number of back jobs it experiences as well as its image of being high-priced. In assessing the company's performance in line with its mission, the group evaluated the CRD (Customer Relations Department) reports of the company. These reports contain customer feedback, reactions and complaints regarding the service provided by the company. Thus, they basically reflect the company's quality of service from the perspective of the customers, and therefore are a good starting point in determining whether the company was indeed the best service center with the best people. The results of the reports showed several complaints regarding the company's service. Most noticeable was the large number of back jobs encountered by the company. This was mainly by the defective parts used, which seemed contradictory to the company's competitive advantage of using genuine parts from competent foreign suppliers. It turned out that the reason behind this was the frequent stock outs experienced by the company. This forced them to purchase parts of a much lower quality from local suppliers. Due to the huge impact the back jobs have not only on the company's operations and profitability but also on its reputation and image, the group focused on reducing them. And as frequent stock outs turned out to be the root cause of the high number of back jobs, it was selected as the primary problem of study. Several other issues were also addressed as minor problems by the study. Two of these were customer complaints from the CRD reports ? stains on car interiors and poor communication with customers. The others were operational ones: redundant forms and networking problems. The solution for the main problem stemmed from the analysis of the current inventory system. The group then made several recommendations to increase its effectiveness. This included recommendations for more accurate forecasting techniques, improved warehouse operations, addition of inventory personnel and improved flow of information. The group also detailed an inventory system appropriate for the company. It is estimated that the implementation of the recommendations would reduce the number of back jobs by 72%. As for the other problems, several operational recommendations and improvements were generated to address them. Some of these recommendations are expected to improve customers' satisfaction over the company's service, while others are aimed at improving the efficiency of the company's operations. A total systems study would not be complete without an analysis of the environmental management system. The group's study showed that the company was using environmentally sound operations and waste management systems. Several recommendations were still given, however, to improve them. These include improved waste disposal, better environment practices and the use of re-refined oil. To effectively implement the recommendations, the group presented implementation guidelines and schedules. This would guide the company in properly implementing the recommendations and improving its performance. Overall, the group was able to meet the study's objectives of analyzing and evaluating the company and generating appropriate recommendations aimed at improving performance.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Rapide Auto Service Center; Automobiles--Maintenance and repair; Service stations; Automobile repair shops; System design